Report of the Working Group on Fertilizers for the Tenth Plan 2002-2003 to 2006-2007 - Planning Commission (Planning Commission, 2002)
To review the status of the industiy upto and during the Ninth Plan period, alongwith an analysis of growth in demand, demand-supply gap, raw materials and infrastructural limitations, technological improvements, and impact of policy changes made during the period.
Department of Fertilizers Ministry of Chemicals and Fertilizers
Government of India